Handbook of procedures of the Germplasm Health Laboratory. Genetic Resources Program - Cuervo Ibáñez, Maritza; Balcázar, María del Socorro; Ramírez, J.L.; Medina, CA; Martínez, J.; Debouck, Daniel G. (International Center for Tropical Agriculture, 2009)
These Handbooks of procedures are reference documents produced by the Genetic Resources Program staff. They are not formally published documents, but they can be useful tools for genebank curators.